Effect of Sociocultural Attitude Towards Appearance and Self-Esteem on Body Image Dissatisfaction among Working Women - Iqra Qasim (Journal of Peace, Development and Communication, 2021)
The main objective of current study was to find out the effect of sociocultural attitude and self-esteem on body image dissatisfaction among working women. Within the present study survey research design was used. The sample included working women (N = 250). Sample was approached through purposive sampling. Sociocultural Attitude toward Appearance Questionnaire (Schaefer et al., 2015), Rosenberg Self-Esteem Scale (Rosenberg, 1965) and Body Dissatisfaction Scale (Tariq & Ijaz, 2015) were used to collect data and access information from participants. The data was collected through standardized process and analyzed through SPSS-23 version. Descriptive statistics, Pearson correlation, Regression analysis, Independent sample t-test and One-way ANOVA were applied to test the hypothesis. The findings indicated that sociocultural attitude have negative effect on body image dissatisfaction. Another finding indicated that self-esteem has negative effect on body image dissatisfaction among working women. Keywords: Sociocultural attitude, Self-esteem, Body image dissatisfaction